Mensuração de desempenho do ecossistema de inovação para startups - Saccol Filho, Pedro Cezar (2020)
Currently, the environment in which startups operate requires special attention from research and innovation. These ventures allow the generation of jobs and income, boost the economy, and open new markets, but they need an ecosystem that contribute to enhance their activities. Thus, this research aimed at proposing to measure the performance of the innovation ecosystem of the investigated startups, consequently evaluating their levels of competitiveness. In this bibliographic research, it was observed that the startup is a model of a company created to develop a new product or service, in conditions of extreme uncertainty, supported by the ecosystem in which it finds itself, therefore, it was necessary a measurement model to offer information to guarantee the survival of this business model. This way, we answer the following question: How to measure and evaluate the performance levels of the startups’ innovation ecosystem? We used a methodology that included the formation of a modeling that identified the institutional elements considered important in an innovation ecosystem. Thus, an exploratory, descriptive and cross-sectional research was carried out, from ex-post facto applied nature, using the inductive scientific method and qualitative and quantitative approaches, in which the technical procedures included the bibliographic, documentary and survey research. Possible indicators related to the innovation ecosystem were raised, using the assumptions related to the Analytic Hierarchy Process (AHP) methodology. It was allowed through exploratory research taking into account a set of six Fundamental Points of View. With the presented realities, it was stated that “the innovation ecosystem must generate more and better opportunities, providing economic advantages with security, and creating a gravitational force of talents”. Regarding the contributions, this research can be considered as a starting point to conceptualize the innovation ecosystem and, in addition, to develop a viable marketing environment for startups.